Predicting the Dynamic Response of Friction Dissipative Foundations Using a Modified Newmark Model. (2016) - Gorini, Davide Noè; Callisto, Luigi
Abstract: This paper analyses the dynamic behaviour of a seismic isolation technology adopted for the foundations of the towers of two recent long-span bridges, consisting of a dissipative layer of granular soil placed at the contact of the foundation caisson with a group of foundation piles. The fundamental aspects of this isolation device is studied through a three-dimensional modified Newmark model that accounts for the multi-directionality of the seismic motion and includes a simplified description of the dynamic response of the superstructure. This simplified model is expressed in a rigorous non-dimensional formulation and is validated against the results of three-dimensional dynamic analysis of the soil-structure interaction for a specific case of a suspension bridge. Taking advantage of the non-dimensional formulation of the simplified dynamic model, a parametric study of general validity is carried out, that highlights the most significant factors influencing the performance of the dissipative device.